2023
DOI: 10.1021/acs.jpcc.2c09036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Pressure on the Bandgap and the d–d Crystal Field Transitions in Wolframite NiWO4

Abstract: The pressure effects on the optical and structural properties of NiWO4 have been studied experimentally and theoretically. The fundamental bandgap decreases with a pressure coefficient of −12.0 ± 0.2 meV/GPa. Meanwhile, the Ni2+ d–d transition energies increase at a rate of 7.4–14.8 meV/GPa. Therefore, the energy differences between the fundamental band and the Ni2+ d–d transition bands gradually decrease under pressure, which is beneficial to improve its optical performance. These optical phenomena are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 46 publications
9
20
1
Order By: Relevance
“…In Figure a, we present a selection of XRD patterns measured at different pressures. In agreement with ref , we have found that NiWO 4 does not undergo any phase transition in the pressure range covered by our studies, i.e., the crystal structure can be described as isomorphic to wolframite up to 20 GPa. This is supported by the results of Rietveld refinements shown in Figure a at 1.5 and 18.7 GPa.…”
Section: Results and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In Figure a, we present a selection of XRD patterns measured at different pressures. In agreement with ref , we have found that NiWO 4 does not undergo any phase transition in the pressure range covered by our studies, i.e., the crystal structure can be described as isomorphic to wolframite up to 20 GPa. This is supported by the results of Rietveld refinements shown in Figure a at 1.5 and 18.7 GPa.…”
Section: Results and Discussionsupporting
confidence: 93%
“…The pressure dependence of E gap can be well described by a linear function as shown with a red solid line in Figure b. The pressure coefficient of this function, d E gap /d P , is −13(1) meV/GPa, which is in excellent agreement with previous results . The pressure dependence obtained from experiments also agrees with that obtained from our calculations (see Figure b).…”
Section: Results and Discussionsupporting
confidence: 90%
See 3 more Smart Citations